KAJIAN KUAT LEKAT TULANGAN BAMBU PETUNG TAKIKAN TIPE V SEJAJAR DAN TIDAK SEJAJAR DENGAN JARAK TAKIKAN 4 CM DAN 5 CM PADA BETON NORMAL - Bedri Fahrul Churniawan; Agus Setiya Budi; Endah Safitri (Matriks Teknik Sipil, 2014)
The use of steel as a material, combined with the concrete has been done for a long time, this is because each material can becomplementary concrete as a material that is weak against tensile force can be overcome by the presence of a strong reinforcementagainst tensile force and vice versa, so that Reinforced concrete is widely used as a building material until now . But the problem is thereinforcing steel is mined material and unrenewable, so that the longer it will be increasingly depleted. As an alternative try usingreinforcement that cheap, easily available and can be renewed and that the reinforcement of high quality is from bamboo material.This research uses experimental methods to test object used was a concrete cylinder with a diameter of 15 cm and 30 cm high. Thisstudy uses four kinds of variations for the reinforcement of bamboo, bamboo reinforcement petung notch aligned with a distance of 4cm and 5 cm, and bamboo reinforcement petung notch is not aligned with the notch distance of 4 cm and 5 cm. Each specimen 3pieces with type V notch, the notch width 0.8 cm and 0.5 cm depth of the notch. Bamboo reinforcement dimensions length 70 cm,width 2 cm and 0.52 cm thick. As a comparison using steel reinforcement with a diameter of 0.8 cm and a length of 70 cm specimen3 pieces. Quality concrete with f'c = 17.5 planned MPa. Adhesion test performed on a concrete age of 28 days by using a UniversalTesting Machine (UTM).